2006
DOI: 10.1111/j.1463-5224.2006.00452.x
|View full text |Cite
|
Sign up to set email alerts
|

Excision of a feline limbal melanoma and use of nictitans cartilage to repair the resulting corneoscleral defect

Abstract: A limbal melanoma was surgically removed from a 12-year-old castrated male black domestic shorthair (DSH) cat. The resulting full-thickness eye wall defect was repaired using the autologous third eyelid cartilage. The patient was followed for 85 days postoperatively, during which time there was no recurrence. Other than a small amount of fibrin and blood at the anterior lens capsule, no significant complications were seen. Use of the third eyelid cartilage as graft material following resection of a feline limb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Instead of a donor tissue, autogenous tissue has also been used to reduce graft rejection and infection risks. (62) In this case report, conjunctiva from the nictitans vertical cartilage was harvested and secured over the defect after a full thickness sclerotomy and keratotomy to remove a limbal melanocytic tumor from a 12-year-old domestic short haired cat. A small blood clot and fibrin remained on the anterior lens capsule, but no recurrence was observed 85 days postoperatively.…”
Section: Felinementioning
confidence: 99%
“…Instead of a donor tissue, autogenous tissue has also been used to reduce graft rejection and infection risks. (62) In this case report, conjunctiva from the nictitans vertical cartilage was harvested and secured over the defect after a full thickness sclerotomy and keratotomy to remove a limbal melanocytic tumor from a 12-year-old domestic short haired cat. A small blood clot and fibrin remained on the anterior lens capsule, but no recurrence was observed 85 days postoperatively.…”
Section: Felinementioning
confidence: 99%
“…Published cases of primary corneal neoplasms in veterinary species include squamous cell carcinoma, hemangioma, hemangiosarcoma, lymphangioma, lymphangiosarcoma, papilloma, adenocarcinoma, angiokeratoma, and lymphoma . The most common primary corneal neoplasms in veterinary species are viral papilloma and squamous cell carcinoma, predominantly occurring in horses and cattle, and less often in cats and dogs …”
Section: Discussionmentioning
confidence: 99%
“…Multiple risk factors have been identified that increase the incidence of vascular neoplasia of the facial region. Increased exposure to ultraviolet (UV) light has been shown to be a risk factor for the development of vascular tumors of the cornea, bulbar conjunctiva, eyelids including the third eyelid, periocular skin, and skin of the dorsal head, muzzle, and ears in domestic species and research animals . Corneal damage from UV light is represented microscopically by solar elastosis, which appears as a laminar band of dissolution of the superficial collagen fibers and deposition of elastin, which has a blue tinge on hematoxylin and eosin staining, similar to what is seen in dermal collagen with solar elastosis …”
Section: Introductionmentioning
confidence: 97%
“…Although this technique was used to treat a limbal melanoma after excision, this technique could be used for any large eyewall defect. Described corneoscleral grafting techniques are numerous and include autologous grafts using conjunctiva, third eyelid cartilage, fascia lata, biosynthetic grafts, homologous cornea or cornea with sclera, amniotic membrane from a variety of species and prosthetic grafts . Autologous grafts are desirable for corneal surgery because they do not elicit a donor–host rejection reaction.…”
Section: Discussionmentioning
confidence: 99%